High linear gan heterojunction material structure and epitaxial method

CN122909868APending Publication Date: 2026-10-13NO 55 INST CHINA ELECTRONIC SCI & TECHNOLOGYGROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610896009.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]解决的技术问题:本发明提出一种高线性GaN异质结的材料结构及外延方法,能够解决目前现有GaN异质结材料电子气纵深窄、跨导平坦度低的缺陷等的问题

Benefits of technology

[0017]本发明与现有技术相比,其有益效果是:1、在不降低器件跨导峰值及电流密度等性能的基础上,显著展宽沟道电子气的三维纵深,从而改善射频器件的跨导平坦度,适用于高线性GaN射频器件的研制;2、本申请通过上层AlN势垒层、上层GaN沟道层、下层n+AlGaN势垒层、下层GaN沟道层、InGaN背势垒层、n+GaN过渡层的完整六层双沟道与复合沟道一体化结构,实现了电子气面密度1.45×1013cm-2(较常规1.05×1013cm-2提升38%)、电流密度1.5A/mm(较常规1.1A/mm提升36%),同时在栅源电压-8V~0V范围内跨导曲线高而平,跨导峰值~0.46S/mm(较常规~0.40S/mm提升15%),这种面密度、电流密度、跨导峰值和跨导平坦度同步提升的综合效果,不是各特征简单叠加所能预期的;3、通过上层AlN/GaN异质结与下层n+AlGaN/GaN/InGaN/n+GaN复合异质结的双沟道协同设计,以及各层厚度、组分、掺杂浓度的优化匹配,实现了电子气面密度提升、电子气纵深展宽与跨导平坦度改善的同步达成,该技术方案并非本领域技术人员在面对提高GaN异质结线性度这一技术问题时能够轻易想到的;4、电子气三维纵深显著展宽:通过引入GaN/InGaN/n+GaN复合沟道结构及AlN/GaN和AlGaN/GaN双沟道结构,电子气纵向分布显著宽于常规结构,从根本上解决了常规GaN异质结电子气纵深窄(~2nm)的固有问题;5、跨导平坦度大幅改善:本发明器件在栅源电压-8V~0V范围内跨导曲线高而平,跨导平坦度显著优于常规结构,适用于要求高线性度的卫星通信和5G通信应用;6、输出电流密度和跨导峰值同步提升,实现了电流密度、跨导峰值与跨导平坦度的同步改善;7、工艺兼容性好:本发明外延方法基于成熟的MOCVD技术,各工艺步骤与现有GaN HEMT外延工艺兼容,无需特殊设备改造,易于产业化推广。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122909868A_ABST
    Figure CN122909868A_ABST
Patent Text Reader

Abstract

This invention discloses a material structure and epitaxial method for a high linear GaN heterojunction. The material structure, from bottom to top, consists of: a single-crystal substrate, an AlN nucleation layer, a GaN buffer layer, and an n-crystal substrate. + GaN transition layer, InGaN back barrier layer, lower GaN channel layer, lower n + An AlGaN barrier layer, an upper GaN channel layer, and an upper AlN barrier layer are formed. The upper channel is formed at the AlN / GaN heterojunction interface, utilizing the strong polarization and ultrathin properties of the AlN barrier layer to enhance the electron gas surface density and improve pinch-off characteristics. The lower channel is formed at the n... + AlGaN / GaN / InGaN / n + GaN heterojunction interface, where n + AlGaN barrier layer increases electron gas surface density, GaN / InGaN / n + GaN composite channels broaden electron gas depth; This invention significantly broadens electron gas depth while increasing electron gas surface density, making it suitable for the development of high linear GaN RF devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor epitaxial materials technology, specifically relating to a material structure and epitaxial method for a highly linear GaN heterojunction. Background Technology

[0002] GaN high electron mobility field-effect transistors (FETs) offer significant advantages in the radio frequency (RF) field. They achieve high output power and high efficiency while operating stably in various harsh environments, strongly driving system upgrades and replacements, particularly in base station applications. Unlike base stations which require high saturation power, satellite communication demands shielding against electromagnetic interference from other frequency bands. This necessitates that GaN RF devices simultaneously meet high gain and high linearity requirements to achieve wideband data transmission and ensure a high signal-to-noise ratio (SNR). This necessitates a flat transconductance curve. However, conventional GaN RF devices exhibit a typical peak-characteristic transconductance curve. After reaching its peak value at the rising edge, the transconductance decreases with further forward bias of the gate voltage, reducing the channel well depth and rapidly decreasing the channel electron saturation velocity. This leads to significant transconductance degradation, resulting in low transconductance flatness. Furthermore, at high frequencies and input power, the device gain rapidly compresses, intermodulation characteristics deteriorate, and signal amplification distortion and poor linearity occur, failing to meet the requirements of high-performance communication.

[0003] The low transconductance flatness of conventional GaN RF devices is due to the narrow two-dimensional electron gas depth (~2nm) at the GaN heterojunction interface. The transconductance can only maintain a high level within a small gate voltage range before the channel is pinched off. Therefore, the key to improving transconductance flatness is to broaden the three-dimensional depth of the electron gas and achieve a high and flat transconductance curve within a larger gate voltage range. Currently, the mainstream solutions for improving transconductance flatness include multi-channel structures and barrier layer polarization modulation doped structures. Among them, multi-channel structures achieve multiple transconductance peaks based on the principle of top-down, layer-by-layer depletion of channels, thereby improving transconductance flatness. However, the structural design, epitaxial process, and device ring gate process of multi-channel structures are all relatively complex, and the device has high pinch-off voltage and large turn-on voltage, making it difficult to implement. On the other hand, barrier layer polarization modulation doped structures are based on the downward bending of the barrier layer energy band, which causes the electron gas to extend towards the barrier layer, effectively widening the three-dimensional depth of the electron gas and improving transconductance flatness. However, the heterojunction interface of the barrier layer polarization modulation doped structure has a low net polarization charge density, and the alloy has severe disordered scattering, resulting in poor carrier transport characteristics, device transconductance peaks, and output characteristics. In addition to GaN RF device and circuit design, by designing the GaN heterojunction epitaxial material process and structure, the longitudinal broadening of the channel electron gas and the transconductance flatness can be significantly improved without causing other performance degradation. This has important scientific significance and practical value for the application of GaN RF devices in high-frequency satellites and 5G communications. Summary of the Invention

[0004] Technical problem to be solved: This invention proposes a material structure and epitaxial method for a high linear GaN heterojunction, which can solve the defects of narrow electron gas depth and low transconductance flatness in existing GaN heterojunction materials.

[0005] Purpose of the invention: This application designs a new epitaxial structure and epitaxial process, which significantly widens the three-dimensional depth of the channel electron gas without reducing the transconductance peak value and current density of the device, thereby improving the transconductance flatness of the radio frequency device and enhancing the function of GaN radio frequency devices in high-frequency satellite and 5G communication fields.

[0006] The technical solution of this invention: This invention proposes a material structure and epitaxial method for a high linear GaN heterojunction. The material structure, from bottom to top, consists of a single-crystal substrate, an AlN nucleation layer, a GaN buffer layer, and an n... + GaN transition layer, InGaN back barrier layer, lower GaN channel layer, lower n + AlGaN barrier layer, upper GaN channel layer and upper AlN barrier layer.

[0007] An epitaxial method for a high linear GaN heterojunction material structure, comprising the following steps: (1) Select a single crystal substrate and place it on the base inside the MOCVD vapor phase epitaxial growth equipment; (2) Heat the reaction chamber to 1000~1100℃, set the pressure to 50~150 torr, and bake the substrate in a hydrogen atmosphere for 5~15 minutes to remove contaminants from the substrate surface; (3) The reaction chamber is heated to 1100~1250℃, the pressure is set to 30~150 torr, ammonia and aluminum source are introduced, and a 30~200nm thick AlN nucleation layer is grown. The aluminum source is then turned off. (4) In an ammonia atmosphere, the temperature is lowered to 930~1080℃, the pressure is increased to 150~500 torr, a gallium source is introduced, a GaN buffer layer of 0.2~3.0μm thickness is grown, and the gallium source is turned off; (5) In an ammonia atmosphere, while maintaining constant temperature and pressure, a gallium source and silane SiH4 are introduced to grow an n-type doped material with an n-type doping concentration of d1 and a thickness of t1. + GaN transition layer, with gallium source and SiH4 turned off; (6) In an ammonia atmosphere, the temperature is lowered to 750~900℃, the pressure is set to 300~500 torr, and gallium and indium sources are introduced to grow an In alloy with a composition of x2 and a thickness of t2. x2 Ga 1-x2 N-back barrier layer, shutting off gallium and indium sources; (7) The pressure is set to 150~500 torr and the temperature is set to 930~1080℃. During the heating process, the gallium source is introduced to grow a lower GaN channel layer with a thickness of t3. After the temperature is raised to the set temperature, the gallium source is turned off. (8) In an ammonia atmosphere, set the temperature to 950~1100℃ and the pressure to 30~150 torr, introduce gallium source, aluminum source and SiH4, and grow a lower Al layer with an n-type doping concentration of d4, an aluminum alloy composition of x4 and a thickness of t4. x4 Ga 1-x4 N-barrier layer, shutting off gallium source, aluminum source and SiH4; (9) In an ammonia atmosphere, set the temperature to 930~1080℃ and the pressure to 150~500 torr, introduce the gallium source, grow an upper GaN channel layer with a thickness of t5, and then turn off the gallium source. (10) Set the temperature to 950~1100℃ and the pressure to 30~150 torr in an ammonia atmosphere, introduce an aluminum source, grow an upper AlN barrier layer with a thickness of t6, and then turn off the aluminum source. (11) Under ammonia protection, the epitaxial wafer was removed and cooled to room temperature.

[0008] Preferably, the single crystal substrate in step (1) is a silicon carbide single crystal substrate, a sapphire substrate, a silicon substrate, or a gallium nitride substrate.

[0009] Preferably, n in step (5) + GaN transition layer, In in step (6) x2 Ga 1-x2 The N-back barrier layer and the lower GaN channel layer in step (7) constitute GaN / InGaN / n + GaN composite channel structure.

[0010] Preferably, n in step (5) + The GaN transition layer has an n-type doping concentration d1 ranging from 5.0 × 10⁻⁶. 17 cm -3 ~5.0×10 18 cm -3 The thickness t1 ranges from 10 to 40 nm; to allow the electron gas in the lower channel to expand and penetrate into n + The GaN transition layer extends the electron gas depth, and the n-type doping concentration d1 is not less than 5.0 × 10⁻⁶. 17 cm -3 Thickness t1 should not be less than 10nm; to prevent n + Excessive doping in the GaN transition layer can lead to reliability issues such as longitudinal leakage and current collapse in devices. The n-type doping concentration d1 should not exceed 5.0 × 10⁻⁶. 18 cm -3The thickness t1 is not higher than 40nm.

[0011] Preferably, In in step (6) x2 Ga 1-x2 The N-back barrier layer has an In alloy composition x2 ranging from 0.05 to 0.15 and a thickness t2 ranging from 3 to 10 nm. To prevent In precipitation from the InGaN back barrier from deteriorating the material quality and affecting electron mobility, the In alloy composition x2 is not higher than 0.15 and the thickness t2 is not higher than 10 nm. To form a secondary channel at the interface of the lower GaN channel layer / InGaN back barrier layer and broaden the electron gas depth, the In alloy composition x2 is not lower than 0.05 and the thickness t2 is not lower than 3 nm.

[0012] Preferably, the thickness t3 of the lower GaN channel layer in step (7) ranges from 10 to 30 nm; in order to allow the electron gas of the lower channel layer to penetrate into the InGaN back barrier and n + A GaN transition layer is used to extend the electron gas depth, with a thickness t3 not exceeding 30 nm; to prevent the InGaN back barrier layer from being too far from the underlying Al layer... x4 Ga 1-x4 The interface between the N-barrier layer and the underlying GaN channel layer is too close, which can cause reliability issues such as current collapse. The thickness t3 should not be less than 10nm.

[0013] Preferably, in step (8) Al x4 Ga 1-x4 The N-type barrier layer has an n-type doping concentration d4 ranging from 1.0 × 10⁴. 18 cm -3 ~5.0×10 18 cm -3 The aluminum alloy composition x4 ranges from 0.20 to 0.40, and the thickness t4 ranges from 10 to 30 nm; to improve the electron gas surface density of the lower channel, the lower Al layer... x4 Ga 1-x4 The N-type barrier layer employs n-type doping technology, and the doping concentration d4 is not less than 1.0 × 10⁴. 18 cm -3 The aluminum alloy composition x4 is not less than 0.20, and the thickness t4 is not less than 10nm; if the lower layer Al x4 Ga 1-x4 Excessive doping of the N-type barrier layer leads to severe scattering of n-type impurities, significantly impacting channel electrons and causing electron mobility degradation. Therefore, the doping concentration d4 should not exceed 5.0 × 10⁴. 18 cm -3 If the lower layer Al x4 Ga 1-x4 Excessive N-type barrier layer composition and thickness can lead to several problems. Firstly, the enhanced anti-polarization effect reduces the surface density of the electron gas in the upper channel. Secondly, the lower Al layer... x4 Ga 1-x4The increased lattice mismatch stress between the N barrier layer and the underlying GaN channel layer leads to a decrease in the electron mobility of the underlying channel. Therefore, the aluminum alloy composition x4 should not exceed 0.40, and the thickness t4 should not exceed 30 nm.

[0014] Preferably, the thickness t5 of the upper GaN channel layer in step (9) ranges from 8 to 15 nm; to suppress the lower Al layer x4 Ga 1-x4 The thickness t5 of the N-barrier layer should not be less than 8 nm to mitigate the anti-polarization effect of the upper channel electron gas and the disordered scattering of the alloy. To enhance the coupling effect of the upper and lower channel electron gases, improve the transconductance flatness of the device, and simultaneously improve the pinch-off characteristics of the device, the thickness t5 should not be greater than 15 nm.

[0015] Preferably, the thickness t6 of the upper AlN barrier layer in step (10) is in the range of 3~8nm; in order to maintain the high areal density of electron gas in the upper channel, the thickness t6 is not less than 3nm; in order to suppress the lattice mismatch scattering between the upper AlN barrier layer and the upper GaN channel layer and maintain a high electron mobility, the thickness t6 is not higher than 8nm.

[0016] Explanation of the principle: This application describes a dual-channel cooperative working mechanism. The upper channel is formed at the AlN / GaN heterojunction interface. The AlN barrier layer exhibits strong spontaneous polarization and piezoelectric polarization effects (polarization intensity is significantly higher than that of AlGaN), inducing high-density 2DEG at the AlN / GaN interface even with an ultrathin thickness (3~8nm). Simultaneously, the ultrathin AlN barrier layer is beneficial for improving the device's gate control capability and pinch-off characteristics. The lower channel is formed at the n... + AlGaN / GaN / InGaN / n + GaN composite heterojunction interface, n + The AlGaN barrier layer further enhances the polarization charge density at the heterojunction interface through doping, increasing the 2DEG areal density; the electron gas depth extension mechanism is employed, and the underlying channel utilizes GaN / InGaN / n + GaN composite channel structure: The main channel is located between the lower GaN channel layer and the lower n-layer. + AlGaN barrier layer interface; InGaN back barrier layer and underlying GaN channel layer form a secondary channel, allowing electron gas to penetrate into the InGaN layer; n + Doped electrons in the GaN transition layer can diffuse towards the channel, further expanding the electron gas distribution space; the synergistic effect of these three factors causes the electron gas to no longer be confined to a single heterojunction interface (~2nm), but to significantly widen along the longitudinal direction (thickness direction); Channel coupling enhancement mechanism: the thickness of the upper GaN channel layer is designed to be 8~15nm, which is sufficient to suppress the lower n +The AlGaN barrier layer has a negative effect on the anti-polarization of the upper channel electron gas and the influence of alloy disorder scattering. It is also thin enough to achieve the coupling effect between the upper and lower channels. Channel coupling can further improve the flatness of the transconductance curve.

[0017] Compared with the prior art, the beneficial effects of this invention are: 1. Without reducing the transconductance peak value and current density of the device, it significantly widens the three-dimensional depth of the channel electron gas, thereby improving the transconductance flatness of the RF device, and is suitable for the development of high linear GaN RF devices; 2. This application uses an upper AlN barrier layer, an upper GaN channel layer, and a lower n-layer... + AlGaN barrier layer, lower GaN channel layer, InGaN back barrier layer, n + The complete six-layer dual-channel and composite-channel integrated structure of the GaN transition layer achieves an electron gas surface density of 1.45 × 10⁻⁶. 13 cm -2 (Compared to the conventional 1.05×10) 13 cm -2 A 38% improvement), current density of 1.5 A / mm (a 36% improvement over the conventional 1.1 A / mm), and a high and flat transconductance curve within the gate-source voltage range of -8V to 0V, with a peak transconductance of ~0.46 S / mm (a 15% improvement over the conventional ~0.40 S / mm). This combined effect of simultaneous improvement in areal density, current density, peak transconductance, and transconductance flatness cannot be expected by simply adding up individual features; 3. Through the upper AlN / GaN heterojunction and the lower n + AlGaN / GaN / InGaN / n + The dual-channel synergistic design of GaN composite heterojunctions, along with the optimized matching of layer thickness, composition, and doping concentration, achieves simultaneous improvement in electron gas surface density, electron gas depth expansion, and transconductance flatness. This technical solution is not something that those skilled in the art would easily conceive of when facing the technical problem of improving the linearity of GaN heterojunctions; 4. Significantly broadened three-dimensional electron gas depth: By introducing GaN / InGaN / n +The GaN composite channel structure and AlN / GaN and AlGaN / GaN dual-channel structures exhibit a significantly wider longitudinal electron gas distribution than conventional structures, fundamentally solving the inherent problem of narrow electron gas depth (~2nm) in conventional GaN heterojunctions; 5. Significantly improved transconductance flatness: The transconductance curve of the device of this invention is high and flat within the gate-source voltage range of -8V to 0V, and the transconductance flatness is significantly better than that of conventional structures, making it suitable for satellite communication and 5G communication applications requiring high linearity; 6. Simultaneous improvement of output current density and transconductance peak value, achieving simultaneous improvement of current density, transconductance peak value and transconductance flatness; 7. Good process compatibility: The epitaxial method of this invention is based on mature MOCVD technology, and each process step is compatible with existing GaN HEMT epitaxial processes, requiring no special equipment modification and facilitating industrialization. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the high linearity GaN heterojunction material structure of the present invention; Figure 2 This is a schematic diagram of a conventional GaN heterojunction material structure in the prior art; Figure 3 A comparison of the longitudinal distribution curves of the channel electron gas of the high linear GaN heterojunction material provided by the present invention and the conventional GaN heterojunction material grown by existing technology. Figure 4 A comparison of the IV characteristic curves of the devices corresponding to the high linear GaN heterojunction material provided by the present invention and the conventional GaN heterojunction material grown by existing technology. Figure 5 A comparison of transconductance characteristic curves of devices corresponding to the high linear GaN heterojunction material provided by this invention and conventional GaN heterojunction materials grown by existing technology. Detailed Implementation

[0019] The technical solution of the present invention will be described in detail below, but the scope of protection of the present invention is not limited to the embodiments described.

[0020] Example 1, as shown in the attached document Figure 1 As shown, this invention proposes a high-linearity GaN heterojunction material structure and epitaxial method based on a silicon carbide single crystal substrate 1, an AlN nucleation layer 2, a GaN buffer layer 3, and an n-type silicon carbide single crystal substrate 1, an AlN nucleation layer 2, a GaN buffer layer 3, and an n-type silicon carbide single crystal substrate 4. + GaN transition layer 4a, InGaN back barrier layer 4b, lower GaN channel layer 4c, lower n + AlGaN barrier layer 4d, upper GaN channel layer 5a, and upper AlN barrier layer 5b.

[0021] An epitaxial method for a high linear GaN heterojunction material structure, comprising the following steps: Step 1: Select a 4-inch silicon carbide single crystal substrate 1 and place it on the base inside the MOCVD equipment; Step 2: Heat the reaction chamber to 1070℃, set the pressure to 100 torr, and bake the substrate in a hydrogen atmosphere for 10 minutes to remove contaminants from the substrate surface; Step 3: Heat the reaction chamber to 1150℃, set the pressure to 80 torr, introduce ammonia and trimethylaluminum, grow a 50nm thick AlN nucleation layer 2, and then turn off the trimethylaluminum. Step 4: In an ammonia atmosphere, lower the temperature to 1030℃, increase the pressure to 200 torr, introduce trimethylgallium, grow a 1.5μm thick GaN buffer layer 3, and then turn off trimethylgallium. Step 5: Maintain constant temperature and pressure in an ammonia atmosphere, introduce trimethylgallium and SiH4 to grow an n-type doped concentration of 1.0 × 10⁻⁶. 18 cm -3 20nm thick n + GaN transition layer 4a, with trimethylgallium and SiH4 turned off; Step Six: In an ammonia atmosphere, the temperature is lowered to 830℃, the pressure is set to 400 torr, and trimethylgallium and trimethylindium are introduced to grow a 6nm thick In layer. 0.05 Ga 0.95 N-back barrier layer 4b, shutting off trimethylgallium and trimethylindium; Step 7: Set the pressure to 200 torr and the temperature to 1050℃. During the heating process, introduce trimethylgallium to grow a 20nm thick lower GaN channel layer 4c. After heating to 1050℃, turn off the trimethylgallium. Step 8: In an ammonia atmosphere, set the temperature to 1050℃ and the pressure to 80 torr, introduce trimethylgallium, trimethylaluminum, and SiH4 to grow an n-type doped concentration of 1.0 × 10⁻⁶. 18 cm -3 15nm thick lower Al layer 0.3 Ga 0.7 N-barrier layer 4d, shutting off trimethylgallium, trimethylaluminum and SiH4; Step 9: In an ammonia atmosphere, set the temperature to 1050℃ and the pressure to 200 torr, introduce trimethylgallium, and grow an upper GaN channel layer 5a with a thickness of 10nm. Then turn off the trimethylgallium. Step 10: Set the temperature to 1050℃ and the pressure to 80 torr in an ammonia atmosphere, introduce trimethylaluminum, and grow an upper AlN barrier layer 5b with a thickness of 5nm. Then turn off the trimethylaluminum. Step 11: Under ammonia protection, allow the temperature to drop to room temperature, then remove the epitaxial wafer.

[0022] The structure of conventional GaN heterojunction materials grown using existing technologies is shown in the attached figure. Figure 2 As shown, from bottom to top, the layers are: 1. Silicon carbide single crystal substrate; 2. 50 nm thick AlN nucleation layer; 3. 1.5 μm thick GaN buffer layer; 4. 0.15 μm thick GaN channel layer; 5. 20 nm thick Al... 0.3 Ga 0.7 N-barrier layer 4f.

[0023] The electron gas surface density of the high linear GaN heterojunction material provided in this embodiment of the invention is 1.45 × 10⁻⁶. 13 cm -2 The electron gas surface density of conventional GaN heterojunction materials grown using existing technologies is 1.05 × 10⁻⁶. 13 cm -2 This indicates that the strongly polarized AlN barrier layer and the n-type AlGaN barrier layer effectively increased the channel electron gas surface density. The longitudinal distribution of electron gas in the two GaN heterojunction materials is shown in the attached figure. Figure 3 As shown, the longitudinal distribution of the electron gas in the high-linearity GaN heterojunction material is significantly wider than that in conventional GaN heterojunction materials grown using existing techniques, indicating that the introduction of GaN / InGaN / n... + GaN composite channel structures, as well as AlN / GaN and AlGaN / GaN dual-channel structures, can significantly broaden the three-dimensional depth of the electron gas, which is beneficial to improving the transconductance flatness of the device.

[0024] The device IV characteristic curves for the two GaN heterojunction materials mentioned above are attached. Figure 4 As shown, the device current density corresponding to the high linear GaN heterojunction material provided by the present invention is 1.5 A / mm, while the device current density corresponding to the conventional GaN heterojunction material is 1.1 A / mm, indicating that the high linear GaN heterojunction material provided by the present invention can significantly improve the device current density.

[0025] The transconductance curves of the two heterojunction materials mentioned above are attached. Figure 5 As shown, the transconductance curve of the device corresponding to the high linear GaN heterojunction material provided by the present invention is high and flat within the gate-source voltage range of -8V to 0V. The transconductance flatness is better than that of the device corresponding to the conventional GaN heterojunction material grown in the prior art, indicating that the broadening of the three-dimensional depth of the electron gas improves the transconductance flatness. In addition, the transconductance peak value of the high linear AlGaN / GaN heterojunction material is ~0.46S / mm, which is slightly higher than the ~0.40S / mm of the conventional AlGaN / GaN heterojunction material grown in the prior art. This indicates that the device corresponding to the high linear GaN heterojunction material in the embodiments provided by the present invention can maintain a high transconductance peak value while improving the transconductance flatness.

[0026] Compared with conventional GaN heterojunction materials grown using existing technologies, the high-linearity GaN heterojunction material provided in the embodiments of the present invention significantly broadens the three-dimensional depth of the electron gas and simultaneously improves the transconductance flatness of the device while maintaining improved output current density, electron gas surface density and transconductance peak value, thus promoting the improvement of linearity of GaN RF devices.

[0027] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A material structure for a highly linear GaN heterojunction, characterized in that, The material structure, from bottom to top, includes: a single-crystal substrate, an AlN nucleation layer, a GaN buffer layer, and an n-crystal substrate. + GaN transition layer, InGaN back barrier layer, lower GaN channel layer, lower n + AlGaN barrier layer, upper GaN channel layer and upper AlN barrier layer.

2. An epitaxial method for the material structure of a high linear GaN heterojunction as described in claim 1, characterized in that, The steps are as follows: (1) Select a single crystal substrate and place it on the base inside the MOCVD vapor phase epitaxial growth equipment; (2) Heat the reaction chamber to 1000~1100℃, set the pressure to 50~150 torr, and bake the substrate in a hydrogen atmosphere for 5~15 minutes to remove contaminants from the substrate surface; (3) The reaction chamber is heated to 1100~1250℃, the pressure is set to 30~150 torr, ammonia and aluminum source are introduced, and a 30~200nm thick AlN nucleation layer is grown. The aluminum source is then turned off. (4) In an ammonia atmosphere, the temperature is lowered to 930~1080℃, the pressure is increased to 150~500 torr, a gallium source is introduced, a GaN buffer layer of 0.2~3.0μm thickness is grown, and the gallium source is turned off; (5) In an ammonia atmosphere, while maintaining constant temperature and pressure, a gallium source and silane SiH4 are introduced to grow an n-type doped material with an n-type doping concentration of d1 and a thickness of t1. + GaN transition layer, with gallium source and SiH4 turned off; (6) In an ammonia atmosphere, the temperature is lowered to 750~900℃, the pressure is set to 300~500 torr, and gallium and indium sources are introduced to grow an In alloy with a composition of x2 and a thickness of t2. x2 Ga 1-x2 N-back barrier layer, shutting off gallium and indium sources; (7) The pressure is set to 150~500 torr and the temperature is set to 930~1080℃. During the heating process, the gallium source is introduced to grow a lower GaN channel layer with a thickness of t3. After the temperature is raised to the set temperature, the gallium source is turned off. (8) In an ammonia atmosphere, set the temperature to 950~1100℃ and the pressure to 30~150 torr, introduce gallium source, aluminum source and SiH4, and grow a lower Al layer with an n-type doping concentration of d4, an aluminum alloy composition of x4 and a thickness of t4. x4 Ga 1-x4 N-barrier layer, shutting off gallium source, aluminum source and SiH4; (9) In an ammonia atmosphere, set the temperature to 930~1080℃ and the pressure to 150~500 torr, introduce the gallium source, grow an upper GaN channel layer with a thickness of t5, and then turn off the gallium source. (10) Set the temperature to 950~1100℃ and the pressure to 30~150 torr in an ammonia atmosphere, introduce an aluminum source, grow an upper AlN barrier layer with a thickness of t6, and then turn off the aluminum source. (11) Under ammonia protection, the epitaxial wafer was removed and cooled to room temperature.

3. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, The single crystal substrate in step (1) is a silicon carbide single crystal substrate, a sapphire substrate, a silicon substrate, or a gallium nitride substrate.

4. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, n in step (5) + GaN transition layer, In in step (6) x2 Ga 1-x2 The N-back barrier layer and the lower GaN channel layer in step (7) constitute GaN / InGaN / n + GaN composite channel structure.

5. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, n in step (5) + The GaN transition layer has an n-type doping concentration d1 ranging from 5.0 × 10⁻⁶. 17 cm -3 ~5.0×10 18 cm -3 The thickness t1 ranges from 10 to 40 nm.

6. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, In step (6) x2 Ga 1-x2 The N-back barrier layer has an In alloy composition x2 ranging from 0.05 to 0.15 and a thickness t2 ranging from 3 to 10 nm.

7. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, The thickness t3 of the lower GaN channel layer in step (7) ranges from 10 to 30 nm.

8. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, In step (8), Al x4 Ga 1-x4 The N-type barrier layer has an n-type doping concentration d4 ranging from 1.0 × 10⁴. 18 cm -3 ~5.0×10 18 cm -3 The aluminum alloy composition x4 ranges from 0.20 to 0.40, and the thickness t4 ranges from 10 to 30 nm.

9. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, The thickness t5 of the upper GaN channel layer in step (9) ranges from 8 to 15 nm.

10. The epitaxial method for the material structure of a high linear GaN heterojunction according to claim 2, characterized in that, The upper AlN barrier layer in step (10) has a thickness t6 ranging from 3 to 8 nm.